Linguistic and clinical validation of the Turkish version of Acute Cystitis Symptom Score for the diagnosis and patient-reported outcome in acute uncomplicated cystitis - Ersan Arda; Jakhongir Alidjanov; Sinan Ates; Mete Çek; Adrian Piatz; Florian M. Wagenlehner; Kurt G. Naber (Investigative and Clinical Urology, 2023)
Purpose: The Acute Cystitis Symptom Score (ACSS) was developed as a self-reporting questionnaire for diagnosing and monitoring acute uncomplicated cystitis (AC) in female patients. The study aims at the translation of the ACSS into Turkish from the original Uzbek including its linguistic, cognitive and clinical validation. Materials and Methods: After forward and backward translation of the ACSS from Uzbek to Turkish and vice versa, the cognitive assessment of the Turkish ACSS was performed on 12 female subjects to achieve the final study version. Results: The clinical validation was performed on a total of 120 female respondents including 64 Patients with AC and 56 controls without AC. For clinical diagnosis of AC, the predefined summary score of the typical symptoms of >6 showed high values (95% confidence interval) for sensitivity (0.88 [0.77–0.94]), specificity (0.98 [0.91–1.00]), and diagnostic accuracy (0.93 [0.86–0.97]). All patients were followed up between five to nine days after the baseline visit. Forty-four (68.75%) patients used antimicrobial treatment, whereas the rest (31.25%) preferred non-antimicrobial treatment. The severity scores of the typical symptoms and the quality of life were reduced significantly at follow-up. Using different (favored) thresholds for successful and non-successful treatment a clinical success rate between 54.7% and 64.1% (60.9%) was achieved. Conclusions: After translation from the original Uzbek and cognitive assessment, the Turkish ACSS showed similar good results for clinical diagnosis and patient-reported outcome as in other languages validated so far and could therefore now be used for clinical studies as well as in everyday practice.